The League of Nations - Henig, Ruth B. (Ruth Beatrice) (Haus histories, 2010)
Ninety years ago the League of Nations convened for the first time, hoping to settle disputes by diplomacy, not war. Failure to prevent World War II led to its dissolution and the subsequent creation of the United Nations. Can the United Nations & rsquo; fate be ascertained by reading the history of its predecessor?